Kecemasan Atlet Bulutangkis Menjelang Turnamen pada Atlet Bulutangkis Dibawah Naungan PBSI Kota Jambi - Muhammad Rizky; Marlita Andhika Rahman; Annisa Andriani (CV. Lentera Literasi Indonesia, 2026)
Anxiety is one of the psychological factors that influences badminton athletes' performance before tournaments. Athletes often experience pressure related to performance expectations, concerns about match outcomes, and physiological reactions, yet comprehensive empirical data on athletes' anxiety levels in Jambi City remains limited. This study aimed to describe the level of anxiety of badminton athletes approaching tournaments in Jambi City based on somatic anxiety, cognitive anxiety, and self-confidence. A quantitative descriptive approach was used. The population consisted of 530 active badminton athletes registered under PBSI Jambi City, with 84 athletes selected through purposive sampling. Data were collected using the Competitive State Anxiety Inventory-2 Revised (CSAI-2R) Indonesian version and analyzed descriptively using SPSS version 28. Results showed that the majority of athletes were in the moderate anxiety category (59.5%), followed by the low (31.0%) and high (9.5%) categories. Somatic anxiety emerged as the most dominant aspect, indicated by physical symptoms such as body tension, rapid heartbeat, and stomach discomfort. Cognitive anxiety appeared at a moderate level, reflecting concerns about performance and outcomes, while self-confidence remained relatively stable but fluctuated according to competitive pressure. These findings provide an empirical basis for developing structured mental training programs for badminton athletes at the regional level.